“Real versus ideal”: Utopia and the Early Modern Satirical Tradition - Renner, Bernd (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2018)
Building on previous studies of satire in Thomas More’s Utopia, this article aims at situating More’s founding text of utopian literature more firmly in the early modern satirical tradition, a tradition that gradually dissociated itself from its conventional generic definition informed by classical Roman verse satura. Key concerns of the analysis touch on the pedagogical function, the dialogic engagement with the reader, and the social reforming spirit that transform satire into a mode and help it incorporate the utopian mindset into its characteristic juxtaposition of blame (of a heavily flawed reality) and praise (of a desirable ideal state of existence). More’s masterpiece is essential in illustrating and promoting this development of early modern satire, as references to an immediate predecessor—the Ship of Fools corpus—as well as a famous successor—François Rabelais—demonstrate.